1995
DOI: 10.3109/00016489509139346
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Airway Pressure Recording in Sleep Apnea Syndrome

Abstract: A comparison was made between polysomnographic recordings and recordings of airflow pressures in the pharynx and respiratory pressures in the esophagus of 10 adult sleeping subjects with differing degrees of apnea. Pressure measurements were obtained by microsensors mounted on a 7F gauge flexible catheter which sited them in the epi-, meso- and hypopharynx and the esophagus. Digitized overnight pressure data were stored on a PC memory card and subsequently displayed for analysis by means of a notebook computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
4

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 8 publications
0
24
0
4
Order By: Relevance
“…UA pressure measurements provide information about UA dynamics in terms of changes in UA pressure before, during and after the appearance of respiratory events. Results from UA pressure measurements have been reported by several authors using different techniques varying from a fluid-filled catheter [5] to movable catheters [6,7], a bias flow catheter [8][9][10] and micropressure sensors [11][12][13][14][15]. Most studies were performed in a limited number of patients (n<20) except those of KATSANTONIS et al [15], SCATVEDT [13] and METES et al [7].…”
mentioning
confidence: 99%
“…UA pressure measurements provide information about UA dynamics in terms of changes in UA pressure before, during and after the appearance of respiratory events. Results from UA pressure measurements have been reported by several authors using different techniques varying from a fluid-filled catheter [5] to movable catheters [6,7], a bias flow catheter [8][9][10] and micropressure sensors [11][12][13][14][15]. Most studies were performed in a limited number of patients (n<20) except those of KATSANTONIS et al [15], SCATVEDT [13] and METES et al [7].…”
mentioning
confidence: 99%
“…This method continuously monitors changes of pressure (at the mesopharynx and esophagus) and temperature (at epi-and hypopharynx) through a flexible 2-mm catheter with transducers. Another 4 channels store: oxygen saturation (SaO 2 ), heart rate, body position and snoring sounds [7] . The objective of this study was to compare PSG and AG by measuring the following parameters: apnea-hypopnea index (AHI), apnea index (AI), hypopnea index (HI), pulse, SaO 2 , body position and the type of apnea (obstructive, mixed and central).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that pressure recordings provide comprehensive diagnostic information in SRBD [10]. The AG device, in the diagnosis of OSA, compares favourably with polysomnography.…”
Section: Discussionmentioning
confidence: 91%